LncRNA SNHG14 potentiates pancreatic cancer progression via modulation of annexin A2 expression by acting as a competing endogenous RNA for miR‐613 - Deng, Peng‐cheng; Chen, Wei‐bo; Cai, Hui‐hua; An, Yong; Wu, Xin‐quan; Chen, Xue‐min; Sun, Dong‐lin; Yang, Yu; Shi, Long‐qing; Yang, Yong (Journal of cellular and molecular medicine, 2019)
This study aimed to determine long non‐coding RNA (lncRNA) small nucleolar RNA host gene 14 (SNHG14) expression in pancreatic cancer and to explore the potential molecular actions of SNHG14 in mediating pancreatic cancer progression. Gene expression was detected by quantitative real‐time PCR. Cell proliferation, growth and invasion were detected by respective CCK‐8, colony formation, and transwell invasion assays. Protein levels were measured by Western blotting. Cell apoptosis and caspase‐3 activity were detected by flow cytometry and caspase‐3 activity assay. The link between miR‐613 and its targets was evaluated by luciferase reporter assay. In vivo tumour growth was evaluated using a xenograft model of nude mice. SNHG14 expression was up‐regulated in cancerous tissues from pancreatic cancer patients. High expression of SNHG14 was associated with poor tumour differentiation, advanced TNM stage and nodal metastasis. SNHG14 overexpression enhanced cell proliferative, growth and invasive abilities, and suppressed apoptotic rates and caspase‐3 activity in pancreatic cancer cells, while SNHG14 knockdown exerted opposite effects. Mechanistic studies revealed that miR‐613 was targeted by SNHG14, and Annexin A2 (ANXA2) was targeted and inversely regulated by miR‐613 in pancreatic cancer cells. In vivo studies showed that SNHG14 knockdown attenuated tumour growth. MiR‐613 was down‐regulated and ANXA2 was up‐regulated in the pancreatic cancer tissues, and SNHG14 expression levels were inversely correlated with miR‐613 expression levels and positively correlated with the ANXA2 mRNA expression levels. Collectively, our results suggest that SNHG14 potentiates pancreatic cancer progression through modulation of annexin A2 expression via acting as a competing endogenous RNA for miR‐613.